2010
DOI: 10.1016/j.ccl.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Principles and Techniques of Blood Pressure Measurement

Abstract: Although the mercury sphygmomanometer is widely regarded as the “gold standard” for office blood pressure measurement, the ban on use of mercury devices continues to diminish their role in office and hospital settings. To date, mercury devices have largely been phased out in US hospitals. This has led to the proliferation of non-mercury devices and has changed (probably for ever) the preferable modality of blood pressure measurement in clinic and hospital settings. In this article, the basic techniques of bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
275
0
21

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(297 citation statements)
references
References 87 publications
1
275
0
21
Order By: Relevance
“…Although the mercury sphygmomanometer is widely known as the gold standard method for office BP measurement, a ban on the use of mercury devices has led to a diminishing of its role in office and hospital settings. 11 Today, mercury devices have largely been phased out in Italian hospitals, which has resulted in a proliferation of non-mercury BP measurement devices. In accordance with previous studies, 12,13 our survey showed that aneroid devices were the most used in IMUs; these devices are considered accurate and recommended for BP measurement in the main guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mercury sphygmomanometer is widely known as the gold standard method for office BP measurement, a ban on the use of mercury devices has led to a diminishing of its role in office and hospital settings. 11 Today, mercury devices have largely been phased out in Italian hospitals, which has resulted in a proliferation of non-mercury BP measurement devices. In accordance with previous studies, 12,13 our survey showed that aneroid devices were the most used in IMUs; these devices are considered accurate and recommended for BP measurement in the main guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Each NIBP device has minor variations in the algorithms used to calculate SBP and DBP, and in speeds of inflation and deflation, so our results might not be entirely reproducible with all other devices. [6][7][8] We used the DASH® 3000 monitor, which is in common use globally. We observed that cuff inflation was more rapid than deflation, especially in the normal compared with the large adult cuff.…”
Section: Discussionmentioning
confidence: 99%
“…Such factors include room temperature, alcohol or nicotine consumption, positioning of the arm, muscle tension, situational distress caused by the measurement process, bladder distension, background noise as well as a variety of observer related factors such as observer-participant gender and ethnic difference, observer digit preference (recording all measurements with numbers ending in 0 and 5) and observer characteristics such as diminished hearing and visual acuity and hand-eye coordination (Pickering et al, 2005). These factors, their effects, and the means to mitigate them (to the extent possible) have been summarized numerous times over the years and rather than reiterate them here the reader should consult these earlier works particularly Ostchega et al (2003), Pickering et al (2005), and Ogedegbe and Pickering (2010). However, there is an important source of error that is related to the sphygmomanometer.…”
Section: Sources Of Error In Blood Pressure Measurementsmentioning
confidence: 99%
“…The standard type of monitor for home or field use is an oscillometric device that records pressure from the brachial artery, and there are several acceptable devices on the market (Pickering et al, 2005 (Ogedegbe & Pickering, 2010;. Much like ambulatory monitors, HBPMs run on 2-4 AA or AAA batteries; hence researchers will need a lot of batteries (or fewer rechargeable batteries) to monitor a sufficient number of participants for a study.…”
Section: Automatic Home or Self Blood Pressure Monitors (Hbpm)mentioning
confidence: 99%